1987
DOI: 10.1007/bf00383854
|View full text |Cite
|
Sign up to set email alerts
|

Nucleo-cytoplasmic ratio in ageing skeletal muscle

Abstract: In order to investigate possible changes in the nucleo-cytoplasmic ratio of the muscle fibres during ageing, samples of quadriceps femoris from 15 normal individuals whose age ranged from 17 to 82 years were studied (autopsy material). The mean lesser diameter and the number and size of the muscle fibre nuclei were calculated using a planimetric technique. It was found that nucleo-cytoplasmic ratio increased significantly after the age of 60 years. This was due to a decrease in the mean fibre size whilst the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

1995
1995
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 5 publications
3
31
1
Order By: Relevance
“…Several cryosection studies of ageing human muscle did not observe decrease in myonuclear profiles in ageing, although the extent of fibre atrophy was not reported (Manta et al, 1987;Renault et al, 2002). By contrast, our results on significantly atrophied old muscle reveal a decline in nuclei/unit length.…”
Section: Fibre Nuclear Number Declines During Ageingcontrasting
confidence: 79%
See 1 more Smart Citation
“…Several cryosection studies of ageing human muscle did not observe decrease in myonuclear profiles in ageing, although the extent of fibre atrophy was not reported (Manta et al, 1987;Renault et al, 2002). By contrast, our results on significantly atrophied old muscle reveal a decline in nuclei/unit length.…”
Section: Fibre Nuclear Number Declines During Ageingcontrasting
confidence: 79%
“…Studies of fibre atrophy conflict on whether domain size is maintained or not (Allen et al, 1997;Allen et al, 1996;Kasper and Xun, 1996;Manta et al, 1987;Mitchell and Pavlath, 2001;Roy et al, 1999;Wada et al, 2002). One reason for confusion might be that cytoplasmic volume/nucleus differs between fibres of different type and increases with fibre size (Bruusgaard et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on MND during animal growth in a single species found no difference in nuclear length with body mass (Galavazi and Szirmai, 1971;Manta et al, 1987;Matthew and Moore, 1987;Rosser et al, 2002). Rosser et al found that throughout chicken development, from neonatal to adult, myonuclei had very similar mean lengths (Rosser et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Myonuclear counts from serial transverse sections of human muscle have shown an increased (Kadi et al, 2004a,b) or constant (Manta et al, 1987) myonuclear number during aging. However, the altered shape and elongation of myonuclei in old age observed in this study, as well as in previous experimental animal studies (Brack et al, 2005;Bruusgaard et al, 2006), may give rise to over-counting myonuclei from cross-sections in old age (Brack et al, 2005).…”
Section: Myonuclear Number and Mnd Sizementioning
confidence: 99%
“…A relationship between the number of myonuclei and fibre size has been reported in trained young (Kadi et al, 1999) and old (Manta et al, 1987;Hikida et al, 2000) individuals, but not in untrained elderly subjects (Hikida et al, 1998), reflecting an aging-and ⁄ or atrophy-related deterioration of this relationship (Ohira et al, 1999). In humans, there are a few reports in the literature on the effects of aging on myonuclear density, describing a constant (Vassilopoulos et al, 1977) or decreased (Manta et al, 1987) cytoplasmic density in old age. In addition, an increased myonuclear density has been observed in elderly men and women, but the study did not correct for muscle fibre size (Kadi et al, 2004a,b).…”
Section: Introductionmentioning
confidence: 99%